A Comparison of Significant Criteria for Parents and Children in Selecting Children\'s Books in Mashhad (تحقیقات اطلاع‌رسانی و کتابخانه‌های عمومی, 2013)
Purpose: The aim of this study is to compare the significant criteria for parents and children in selecting book for children. Methodology: The current work is an applied-evaluative study. The research population consisted of two groups: First, the parents for the children between 7 and 12 years old in Mashhad, whose children were either the members of public libraries or of the Institute for the Intellectual Development of Children and Young Adults (IIDCYA), second, the children who were identical with those mentioned above from age, location and membership points of view. The samples were selected through Cluster Sampling Method. Collecting of data was performed through two questionnaires. The validity of the questionnaires was evaluated by some specialists and their reliability was estimated by Cronbach’s alpha test. The alpha coefficient value in the parents’ questionnaire was 0.89 and in the children’s questionnaire, it was 0.84. Findings: The study determined the parents' and children's viewpoints and their common criteria along with their significant sub-components.  Both of the parents and the children considered nine criteria. The findings also showed the most agreement between the Children’s Books Council criteria and those of children and parents respectively in language quality and writing style, and in illustration quality. On the other hand, the least agreement between children’s and parents’ choices was noticed in presentation quality. The first and the last priorities for the both of the parents and the children were the same: content quality at the top and presentation quality at the bottom of their ranking lists. Furthermore, there is a significant difference between the weight of the children’s criteria and those by the parents. But no difference was observed between the girls and boys and also between the fathers and the mothers in the weight of criteria for selecting children’s books. Originality/Value: The importance of the study is in elucidating the parents and their children criteria for selecting the children's books.